2014
DOI: 10.1007/s12665-014-3076-1
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of relationship between vegetation attributes and soil erosion on hillslopes in the Loess Plateau of China

Abstract: In soil and water conservation research, vegetation is considered to be a primary factor affecting soil erosion. Many studies focus on the relationship between soil erosion and a given attribute of vegetation. Few studies have attempted a comprehensive analysis of vegetation attributes. Thus, the aim of this study is to explain the relationship between vegetation and soil erosion in detail. We studied 104 vegetation plots and 104 soil samples in the Yangjuangou catchment, Loess Plateau, Shaanxi Province, China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…It has thus been suggested that the relationship between the soil 137 Cs inventory and species diversity (SHDI) can be modulated by the vegetation pattern (LSI) (Bautista et al, 2007). To reveal whether similar vegetation patterns can present the relationship between plant diversity (SHDI) and the extent of soil erosion (soil 137 Cs inventory) better than different patterns (Hou et al, 2014), these plots were divided into nine groups. There are more similar vegetation patterns within a group than between groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has thus been suggested that the relationship between the soil 137 Cs inventory and species diversity (SHDI) can be modulated by the vegetation pattern (LSI) (Bautista et al, 2007). To reveal whether similar vegetation patterns can present the relationship between plant diversity (SHDI) and the extent of soil erosion (soil 137 Cs inventory) better than different patterns (Hou et al, 2014), these plots were divided into nine groups. There are more similar vegetation patterns within a group than between groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the relationship between plant diversity and soil erosion can be affected by the vegetation pattern (Bautista et al, 2007). It has been suggested that similar vegetation patterns can be better conditions for determining the relationship between plant diversity and soil erosion than areas with different vegetation patterns (Hou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are uncertainties and contradictions in the relationships between pattern indexes and runoff and soil erosion (Liu et al, 2013;Ludwig et al, 2002;Ouyang et al, 2010). As pattern indexes are interdependent, it is difficult to show how landscape patterns prevent soil erosion using a single pattern index (Bautista et al, 2007;Hou et al, 2014).…”
Section: Application Of Pattern Indexes To Represent Vegetation Spatimentioning
confidence: 99%
“…At the slope scale, due to the development of interrill and rill erosion, in addition to aboveground vegetation cover and litter, plant roots must be considered as a crucial factor (Gyssels et al, 2005). Vegetation distribution patterns determine landscape fragmentation and connectivity, and plant diversity contributes greatly to runoff and sediment yields (Bautista et al, 2007;Hou et al, 2014;Pohl et al, 2009;Wei et al, 2014). Several studies have concluded that topography (e.g., slope gradient and slope length) shapes the effects of vegetation on runoff and sediment (Donjadee and Chinnarasri, 2012;Liu et al, 2012;Sadeghi et al, 2013).…”
Section: Scale Issues On the Relationships Of Vegetation Factors Withmentioning
confidence: 99%
“…Vegetation can decrease sand dune encroachment intensity [40] and soil erosion and create a micro-climate for the local population and their livestock [41,42]. Therefore, vegetation plants enrich organic soil and provide a high capacity to reduce the intensity of soil erosion, thus improving the coherence and quality of soil.…”
Section: Introductionmentioning
confidence: 99%